THE EFFECT OF DEXAMETHASONE ON SPERMATOGONIUM AND SERTOLI CELL OF IPSILATERAL TESTIS IN UNILATERAL TESTICULAR TORSION WISTAR RAT - Efendi, Ferdyan Rachmat; Renaldo, Johan; Djojodimedjo, Tarmono (Indonesian Urological Association, 2018)
Objective: To investigate the effect of dexamethasone on spermatogonium and sertoli cell of ipsilateral testis in unilateral testicular torsion strain wistar rat. Material & Method: Experimental study with post-test only control group design. The present study was conducted on 30 Wistar male rats aged 10 – 12 weeks grouped into 5 groups. Group I was the normal/sham operation group (KN), group II was left testicular torsion for 4 hours group and followed by manual detorsion (K1), group III was left testicular torsion for 10 hours group and followed by manual detorsion (K2), group IV was left testicular torsion for 4 hours group and given dexamethasone 10 mg/kg body weight subcutaneously 30 minutes before manual etorsion (D1), and group V was left testicular torsion for 10 hours group and given dexamethasone 10 mg/kg body weight subcutaneously 30 minutes before manual detorsion. All rats had left orchidectomy 4 hours after detorsion. The number of spermatogonium and sertoli cells were counted in histological seminiferous tubular testis that have obtained Haematoxylin Eosin staining. Data were analyzed by ANNOVA followed by Post Hoc Tukey for spermatogonium and Kruskal Wallis followed by Mann Whitney test for sertoli cell. Differences were considered significant at p <0.05. Results: There was significant difference in the mean number of spermatogonium between K1 & D1 group. Otherwise, there was no significant difference in the mean number of spermatogonium between K2 & D2. There was significant difference in the mean number of Sertoli cells between K1 & D1 group, likewise that between K2 & D2 group. Conclusion: These results suggest that dexamethasone has protective effect in spermatogonium and sertoli cell in testicular torsion for 4 hours.